2021
DOI: 10.3389/frobt.2021.745234
|View full text |Cite
|
Sign up to set email alerts
|

Perception by Palpation: Development and Testing of a Haptic Ferrogranular Jamming Surface

Abstract: Tactile hands-only training is particularly important for medical palpation. Generally, equipment for palpation training is expensive, static, or provides too few study cases to practice on. We have therefore developed a novel haptic surface concept for palpation training, using ferrogranular jamming. The concept’s design consists of a tactile field spanning 260 x 160 mm, and uses ferromagnetic granules to alter shape, position, and hardness of palpable irregularities. Granules are enclosed in a compliant vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The study of the psychophysical perception of distributed pressure forces upon exploration by fingertips has long been of interest [7,[19][20][21][22][23]. Rørvik and co-authors [24] investigated whether untrained people could locate and determine by palpation the shapes and hardness of irregularities rendered between two compliant layers by using the ferrogranular jamming principle.…”
Section: Research On Force Feedback Applications At Jnd Levelmentioning
confidence: 99%
“…The study of the psychophysical perception of distributed pressure forces upon exploration by fingertips has long been of interest [7,[19][20][21][22][23]. Rørvik and co-authors [24] investigated whether untrained people could locate and determine by palpation the shapes and hardness of irregularities rendered between two compliant layers by using the ferrogranular jamming principle.…”
Section: Research On Force Feedback Applications At Jnd Levelmentioning
confidence: 99%
“…hand bone protrusions palpation † † [83] Virtuose 6D Desktop, Haption; 3D printed haptic phantom hand 3D printed haptic phantom hand phantom hand 3D printed with stratasys printer (bone: VeroBlackPlus; tissue: a support-material (SUP) and TangoPlus filled metamaterial) sensorized abdominal phantom for palpation training [84] multi-layer abdominal model with controllable organ with positive granular jamming tumors also as sensors to detect palpation force and trajectory 5 controlled nodules (controlled between 30-55 kPa stiffness) within the silicone liver, tissue, and skin model; testing trial with linear indentation palpation showed an RMSE of 4 mm (in the testing area around 100 × 100 mm) and 1.18 N (for the applied force up to 18 N) for the position and force estimation of palpation, respectively. haptic surface † [85] tactile field with granular jamming of ferromagnetic granules to render shape, position, and hardness of palpable irregularities 260 x 160 mm; manipulated with permanent magnets haptic mouse † [86] a mouse type haptic display for localized physical abdomen simulation and interaction to a virtual abdomen different types of granular jamming and layer jamming mechanisms are tested to simulate the muscle guarding. granular jamming structures with soft, fine, and rigid granules, and layer jamming structures with stretchable and non-stretchable layers.…”
Section: B Tactile Displays For Cutaneous Feebackmentioning
confidence: 99%
“…Sensors are needed to capture important data during training sessions, actuators will be used to generate realistic responses, and algorithms are necessary to analyse the data and deliver the feedback in real time. Haptic feedback setups for palpation application range from modelling tumours using granular jamming ( Rørvik et al, 2021 ) to physical systems using interchangeable organs ( Rethy et al, 2018 ). Some physical simulators also produce visual cues, such as the physical–virtual hybrid face rendering pain facial expressions ( Lalitharatne et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%